Modeling Sustainable Consumer Behavior among Generation Z in Bogor City - Rumna; Hari Gursida; Doni Wihartika (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2026)
Purpose – This study develops and tests an integrative model of sustainable consumer behavior (SCB) among Generation Z in Bogor City by examining the influence of Emotional Intelligence (EI), Social Influence (SI), and Perceived Value Alignment (PVA) on SCB through Sustainable Consumer Intention (SCI) mediation. Theoretically, this research extends the Theory of Planned Behavior (TPB) by integrating affective, social, and value alignment dimensions. Design/methodology/approach – This quantitative research uses a survey of 401 Generation Z students in Bogor City which was analyzed with SEM-PLS. Finding/Results – The results showed that EI and PVA had a significant positive effect on SCI and SCB, while SI had no direct effect on SCB. The model demonstrated a very high predictive ability for sustainable consumer behavior (0.873), indicating that the influence of external factors and emotional capacity is mediated by behavioral intentions before manifesting in sustainable consumption actions. SCI emerged as the most dominant mediator, confirming the critical role of behavioral intentions in translating social influences into sustainable consumption behavior. Originality/Value – This research provides an integrative framework that extends TPB by combining EI, SI, and PVA to explain sustainable consumer behavior, offering theoretical insights and practical implications for promoting sustainable consumption among Generation Z.